2018
DOI: 10.1021/acs.jafc.7b04565
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of DHA-PC against Vancomycin-Induced Nephrotoxicity through the Inhibition of Oxidative Stress and Apoptosis in BALB/c Mice

Abstract: The clinical use of glycopeptide antibiotic vancomycin is usually accompanied by nephrotoxicity, limiting its application and therapeutic efficiency. The aim of this study was to investigate the protection of DHA-enriched phosphatidylcholine (DHA-PC) against nephrotoxicity using a model of vancomycin-induced male BALB/c mice with renal injury by measuring death curves, histological changes, and renal function indexes. The addition of DHA in DHA and DHA-PC groups were 300 mg/kg per day on the basis of human int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 50 publications
2
35
0
Order By: Relevance
“…These studies have been reviewed in detail 111 . Since then, spirulina and pycnogenol , 112 mitoTEMPO, naringenin, 113 a free radical scavenger zingerone, 114, 115 DHA‐enriched phosphatidylcholine (DHA‐PC), 116 rutin, 117 and silymarin 118 have been evaluated in animal studies. In our opinion, the antioxidants that are most ready for clinical trials include preparations that are already clinically available, such as atorvastatin, vitamin C, vitamin E, N‐acetylcysteine, erythropoietin, and erdosteine.…”
Section: Potential Strategies For Preventionmentioning
confidence: 99%
“…These studies have been reviewed in detail 111 . Since then, spirulina and pycnogenol , 112 mitoTEMPO, naringenin, 113 a free radical scavenger zingerone, 114, 115 DHA‐enriched phosphatidylcholine (DHA‐PC), 116 rutin, 117 and silymarin 118 have been evaluated in animal studies. In our opinion, the antioxidants that are most ready for clinical trials include preparations that are already clinically available, such as atorvastatin, vitamin C, vitamin E, N‐acetylcysteine, erythropoietin, and erdosteine.…”
Section: Potential Strategies For Preventionmentioning
confidence: 99%
“…The mitochondrial apoptosis pathway played an increasingly great role in drug-induced nephrotoxicity [ 22 ]. An large number of studies have shown that vancomycin treatment could increase the expression of pro-apoptotic proteins (Bax, Cyt-C, Caspase 3, and Caspase 9) and decrease the expression of the Bcl-2 protein [ 12 ]. Our results suggested that the administration of DHA-acylated AST diesters was more effective than the recombination of unesterified AST and DHA in increasing the expression of Bcl-2 protein and inhibiting the expression of several apoptotic proteins, especially the changes of Bax and cleaved-Caspase 3.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that AST esters had better biological activities, including anti-cancer activity, liver protection, and antioxidant function compared with unesterified AST [ 10 ]. A great number of animal and clinical data have shown that DHA possessed a significant alleviation on kidney disease [ 11 , 12 ]. Our previous research showed that dietary supplementation with DHA-acylated AST diester could alleviate the behavioral deficits in the mice with Parkinson’s disease and cognitive disorders in model mice of Alzheimer’s disease, which was better than that of unesterified AST [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic injury was evaluated using the following parameters: bile-duct proliferation, nuclear condensation, hepatocyte necrosis, fatty degeneration, and inflammatory cell infiltration ( Kraieski et al., 2017 ; Ma et al., 2012 ). The pathological changes in kidneys were assessed by renal tubular dilatation and atrophy, hyaline vacuolar degeneration, and tubular epithelial cell swelling or necrosis ( Ma et al., 2018 ; Shi et al., 2018 ). Intestinal morphology analyses were carried out on 2 cross-sections per sample, 15 well-oriented villus per section (30 intact well-oriented villus per sample) were measured ( Poloni et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%